LITERATURE REVIEW: MODEL CONTINUITY OF CARE PELAYANAN KEBIDANAN DEPRESI POSTPARTUM - Utari, Dyah Ayu; Fitria, Nurhidayah (Institut Kesehatan dan Teknologi Al Insyirah, 2024)
During the postpartum period, midwives not only assess the physical examination and breastfeeding process, but also must assess the emotional well being and social support of the postpartum mother. The Continuity of Care (CoC) midwifery care model makes mothers get to know their caregivers better, this is one of the midwifery care models that provides services to help women build relationships with their caregivers. Postpartum depression is a major health problem, having a dangerous impact on postpartum mothers, their babies, and their families. The prevalence of depression in the Southeast Asia region is 27%, while in Indonesia the prevalence of depression is 3.7% and ranks second after India at 4.5%. This study aims to determine the Continuity of Care model for midwifery services with postpartum depression. The type of research used in this research is literature review research using 5 journals from the sources used in the form of journal search studies in electronic databases such as the Directory of Open Access Journals (DOAJ), ScienceDirect and EBSCO in full text form. So it can be concluded that a strong relationship between mothers and midwives who are known for providing continuous care, results in increased trust, more personal and loving care, and better sharing of information will reduce postpartum depression. To address knowledge gaps and methodological deficiencies in the existing literature, articles on postpartum depression in Asian countries need to further explore the role of physical, biological and cultural factors.